Early Precambrian Rocks of Granitic Composition - Krupicka, J. (Canadian Journal of Earth Sciences, 1975)
The granitoids and the corresponding gneisses of the old sialic crust are not exclusively represented by rocks of tonalitic and granodioritic composition. Potassium-rich rocks of true granitic composition occur even in the oldest known complexes of the Earth's crust.The petrography of six samples (39 individual specimens) from the southwestern part of the Early Precambrian Amitsoq gneiss complex in the Godthaab area in Greenland, collected for dating purposes, and of 12 Early Precambrian granitoid pebbles from the basal Moodies conglomerate in South Africa shows that (a) half of the investigated samples of the Amitsoq gneiss, and (b) ten of the Moodies granitoid pebbles are rocks of true granitic composition. The rocks show no evidence of sedimentogenic origin.